The transcription factor AtMYB12 is part of a feedback loop regulating cell division orientation in the root meristem vasculature. (18th January 2023) - Wybouw, Brecht; Arents, Helena E; Yang, Baojun; Nolf, Jonah; Smet, Wouter; Vandorpe, Michael; Minne, Max; Luo, Xiaopeng; De Clercq, Inge; Van Damme, Daniël; Glanc, Matouš; De Rybel, Bert
Abstract: Transcriptional networks are crucial to integrate various internal and external signals into optimal responses during plant growth and development. In Arabidopsis thaliana, primary root vasculature patterning and proliferation are controlled by a network centred around the basic Helix-Loop-Helix transcription factor complex, formed by TARGET OF MONOPTEROS 5 (TMO5) and LONESOME HIGHWAY (LHW), which control cell proliferation and division orientation by modulating the cytokinin response and other downstream factors. Despite recent progress, many aspects of the TMO5/LHW pathway are not fully understood. In particular, the upstream regulators of TMO5/LHW activity remain unknown. Here, using a forward genetics approach to identify new factors of the TMO5/LHW pathway, we discovered a novel function of the MYB-type transcription factor, MYB12. MYB12 physically interacts with TMO5 and dampens the TMO5/LHW-mediated induction of direct target gene expression, as well as the periclinal/radial cell divisions. The expression of MYB12 is activated by the cytokinin response, downstream of TMO5/LHW, resulting in a novel MYB12-mediated negative feedback loop that restricts TMO5/LHW activity, to ensure optimal cell proliferation rates during root vascular development. Abstract : A forward genetics screen in Arabidopsis identifies MYB12 as a repressor of TMO5/LHW activity, ensuring optimal cell proliferation rates during root vascular development.